Analisis Sistem, Problematika, Dan Kebijakan Pendidikan Di Brunei Darussalam Serta Perbandingan Dengan Pendidikan Di Indonesia - Ika Kurnia Sofiani; Mazlin Mazlin; Nuratika Nuratika; Sofia Erlinda; Pebriardi Surya Pamungkas (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to analyze the education system, identify the problems faced, and analyze education policies in Brunei Darussalam, with a special comparison to education in Indonesia. Brunei Darussalam and Indonesia have different cultural, social, economic and political contexts, which influence the structure and implementation of their education systems. The research method used is descriptive and comparative analysis, utilizing secondary data from various literature sources, policies and educational reports. The results of the analysis show that Brunei Darussalam's education system is unique, with a focus on Islamic education and national values. However, several problems such as gaps in educational access and teaching quality are still challenges. On the other hand, Indonesia has a more complex education system with various challenges, including regional disparities, teacher quality, and limited educational infrastructure. A comparison between the two countries highlights differences in policy approaches, educational structures, and challenges faced. Brunei Darussalam emphasizes quality education and strengthening national identity, while Indonesia struggles with the challenges of inclusion and social inequality. The implication of this analysis is the importance of understanding the local context in designing educational policies that are effective and relevant to the needs of local communities. This study provides insight for policy makers to improve the education system and improve the quality of education in both countries.